Pembelajaran Ability Grouping Dalam Mengembangkan Prestasi Akademik dan Non-Akademik Peserta Didik - Nurul 'Aini, Robi'ul Afif (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2024)
This research examines the implementation of ability grouping learning in developing student achievement both in terms of increasing academic and non-academic achievement at Madrasah Ibtidaiyah Darussalam Ngoro Jombang. This research uses a qualitative approach, while the type of research is a case study, as well as data collection techniques using observation, interviews and documentation which the researcher will later explain in data analysis including data reduction, data display and drawing conclusions. The research used several validity checking techniques that the researchers examined, including: Credibility, transferability, confirmability and anteriority. The results of research related to ability grouping include: 1) the planning for ability grouping at MI Darussalan is based on previous teaching staff and the initiative of the madrasa head to develop student achievement by means of ability grouping; 2) the stage of implementing ability grouping at MI Darussalam Badang, namely that each class is divided into 2 groups, namely the superior Ar-Rahman class and the regular Ar-Rahim class. For superior classes there are various kinds of superior programs, and for Ar-Rahim classes it is focused on learning material; 3) the positive impact of ability grouping is that student achievement increases, and the negative impact is that there are still students who feel differentiated from superior classes; 4) The ability grouping evaluation is carried out every semester and at the beginning of the year before the start of the new school year.